2015
DOI: 10.1155/2015/382315
|View full text |Cite
|
Sign up to set email alerts
|

Outcome following Resection of Biliary Cystadenoma: A Single Centre Experience and Literature Review

Abstract: Background. Biliary cystadenomas (BCAs) are rare, benign, potentially malignant cystic lesions of the liver, accounting for less than 5% of cystic liver tumours. We report the outcome following resection of biliary cystadenoma from a single tertiary centre. Methods. Data of patients who had resection of BCA between January 1993 and July 2014 were obtained from liver surgical database. Patient demographics, clinicopathological characteristics, operative data, and postoperative outcome were analysed. Results. 29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Treatment of BCTs must be surgical resection whenever possible due to a potential malignant degeneration of these lesions. 18 19 In the present study, all patients received surgical resection including liver resection or complete cyst excision. Many investigations, including this study, showed that post-resection prognosis of BCA and BCAC is very favourable if complete surgical resection (R0 resection) is performed.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of BCTs must be surgical resection whenever possible due to a potential malignant degeneration of these lesions. 18 19 In the present study, all patients received surgical resection including liver resection or complete cyst excision. Many investigations, including this study, showed that post-resection prognosis of BCA and BCAC is very favourable if complete surgical resection (R0 resection) is performed.…”
Section: Discussionmentioning
confidence: 99%
“…The enigma of this present case revolves whether its origin from liver or pancreas, hence determining the choice of surgical intervention and patient's overall outcomes (8). The surgical intervention in liver pathology only renders on liver resection specifically left hemihepatectomy as in this reviewed case.…”
Section: Discussionmentioning
confidence: 93%
“…As an extracted monomer of plants, PTS has also been proven to have antitumor effects in various cancers, including cancers of the bladder 20 , lung 17 , breast 12 , 13 , prostate 14 , lymphomas 21 , and oral mucosa 22 . The potential mechanisms of PTS include inhibiting tumor cell proliferation and migration 15 , 20 , 21 , inducing cell cycle arrest 12 , 21 , accelerating apoptosis 12 , 17 , 21 , 22 , and inhibiting metastasis 40 , 41 . Moreover, PTS can inhibit the EMT process of breast cancer with the long non-coding RNAs 42 .…”
Section: Discussionmentioning
confidence: 99%